1990
DOI: 10.1093/nar/18.24.7397
|View full text |Cite
|
Sign up to set email alerts
|

Loosened nucleosome linker folding in transcriptionally active chromatin of chicken embryo erythrocyte nuclei

Abstract: We have investigated the mechanism of the electrophoresis-driven chromatin aggregation which had been described by Weintraub (1984, Cell 38, 17-27) as a putative mean for propagation of genetic repression in eukaryotes. We show that the oligonucleosome aggregates are assembled de novo at the starting zone of DNP electrophoresis. A new system of native two-dimensional DNP electrophoresis has been worked out to separate the oligonucleosome aggregates ('A' particles) and the freely-migrating oligonucleosomes ('B'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…H1 is thought to be nearly ubiquitous in the genome, but several studies report its consistently higher abundance in heterochromatin (2224). We propose that higher concentrations of H1, equal in stoichiometry to nucleosomes, along extended chromatin domains may be essential to achieve its optimal function as a repressor, whereas substoichiometric or local deposition may only allow for a limited ability to repress genetic activity in euchromatin (Fig.…”
mentioning
confidence: 99%
“…H1 is thought to be nearly ubiquitous in the genome, but several studies report its consistently higher abundance in heterochromatin (2224). We propose that higher concentrations of H1, equal in stoichiometry to nucleosomes, along extended chromatin domains may be essential to achieve its optimal function as a repressor, whereas substoichiometric or local deposition may only allow for a limited ability to repress genetic activity in euchromatin (Fig.…”
mentioning
confidence: 99%
“…Besides being developmentally regulated, histone H5 shows a preferential association with repressed and condensed chromatin as demonstrated by both biochemical fractionation (Ridsdale and Davie 1987;Grigoryev et al 1990) and CHIP (Kamakaka and Thomas 1990;Postnikov et al 1991). The area of histone H5 depletion over the active chicken β-globin cluster coincides with increased histone acetylation and DNase I sensitivity, thus suggesting a common molecular mechanism regulating spreading of the heterochromatin-associated structural changes at the boundaries of active and repressed chromosomal domains (Verreault and Thomas 1993).…”
Section: Linker Histones and Their Variants Involved In Chromatin Conmentioning
confidence: 92%
“…10 mM monovalent cation. However, upon the gradual increase of ionic strength to 50-80 mM, oligonucleosomes undergo an increasing self-association giving rise to soluble selfassociated chromatin (SAC) particles notably bigger in size than the individual polynucleosome chains (Weintraub 1984;Jose et al 1987;Grigoryev et al 1990;Kamakaka and Thomas 1990). Upon further increase in salt concentration, the progressing self-association culminates in aggregation and precipitation of chromatin.…”
Section: Compaction Above the 30-nm Level: Self-association And Side-mentioning
confidence: 99%
See 1 more Smart Citation
“…To compare Arabidopsis linker lengths with those from other taxa, linker lengths were collated from the literature (Table 4. Previous studies have demonstrated differences in linker length between cells types exhibiting different transcriptional activity (Grigoryev et al, 1990). As the data presented here are generated from many cell types (within an organ), it is likely that multiple chromatin conformations are represented.…”
Section: Relationship Between Linker Length and Intron Lengthmentioning
confidence: 93%